2021
DOI: 10.1109/access.2021.3056035
|View full text |Cite
|
Sign up to set email alerts
|

A Fair Pricing Mechanism in Smart Grids for Low Energy Consumption Users

Abstract: Based on energy demand, consumers can be broadly categorized into low energy consumers (LECs) and high energy consumers (HECs). HECs use heavy load appliances, e.g., electric heaters and air conditioners, and LECs do not use heavy load appliances. Thus, HECs demand more energy compared to LECs. The usage of high energy consumption appliances by HECs leads to peak formation in various time intervals. Different pricing schemes, i.e., time of use (ToU), real time pricing (RTP), inclined block rate (IBR), and crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…It will ensure that energy output and use are in order. The consumer engages in SG services by shifting demand from maximum to off-hours and conserving resources and saving money on energy [3]. DSM allows customers to monitor their energy usage patterns based on the price set by the utility.…”
Section: Smart Gridmentioning
confidence: 99%
“…It will ensure that energy output and use are in order. The consumer engages in SG services by shifting demand from maximum to off-hours and conserving resources and saving money on energy [3]. DSM allows customers to monitor their energy usage patterns based on the price set by the utility.…”
Section: Smart Gridmentioning
confidence: 99%
“…The authors identified a trade-off between cost reduction and comfort maximization and developed a Game theoretic-based algorithm to overcome this trade-off. In [32], the authors proposed a new pricing mechanism for low and high energy consumption users based on a time of use pricing policy. The price signal is further divided into different blocks and forecasted load is scheduled based on these prices to curtail the cost of end users.…”
Section: Related Workmentioning
confidence: 99%
“…In order to benefit from the DR programs, a home energy management system (HEMS) must be installed in the home. 7 The scheduling of residential appliances is optimized, the ESS/EV is managed, and customers profit financially due to the adoption of HEMS. It also achieves a decent balance between power prices and the home's peak to average ratio (PAR).…”
Section: Introductionmentioning
confidence: 99%